The dental health and technology. Contributions and contradictions - Zhenia Véliz Águila; Virgina Pentón García; Bárbara Prado Lemus; Isabel Noriega Cabrera; Limaisi Brunet Herrera; Irma Sueiro Sánchez (Medisur)
The situation of the Stomatology in the contemporary world demands to the society the recognition technology needs as a key factor for their development. Presently article is meditated on the narrow existent relationship between the terms information, technology and health in Stomatology and some contradictions that reveal the importance of understanding the techno-science, demonstrating the importance of this relationship as the basis and driving force which will result in the development related to health, which will help to improve every day functioning and quality of dental services.